Human-Centered Residential Architecture in the Post-COVID Era: Exploring Developments and Significance - Georgi Stoyanov (Athens Journal of Health and Medical Sciences, 2023)
This study investigates the developments and significance of human-centered residential architecture in the post-COVID era, focusing on how the pandemic has shaped architectural design better to accommodate inhabitants' evolving needs and well-being. The research employs a mixed-methods approach, combining a comprehensive literature review, expert interviews, and case studies of innovative residential projects. The literature review highlights the fundamental principles of human-centered design, emphasizing the importance of flexibility, adaptability, and the integration of outdoor and indoor spaces. Expert interviews with architects and urban planners provide insights into the challenges and opportunities faced in developing residential projects during and after the pandemic. At the same time, case studies showcase successful examples of human-centered architecture addressing the unique demands of the post-COVID context. Results indicate that the COVID-19 pandemic has accelerated the adoption of human-centered design principles in residential architecture, improving occupants' mental and physical health, enhancing social interactions, and promoting sustainability. Key findings reveal an increased emphasis on flexible living spaces, biophilic design elements, and technology integration to support remote work and communication. Furthermore, the study underscores the role of community-based amenities and shared spaces in fostering a sense of belonging and resilience. The research contributes to the growing knowledge of human-centered residential architecture post-COVID. It highlights the significance of addressing the changing needs of inhabitants to promote well-being and adaptability in an increasingly unpredictable world. The findings have practical implications for architects, urban planners, and policymakers designing and developing future residential projects.